Intention to use reusable bags among hypermarket customer in Sungai Petani /Nur lzzatul Asma Mohammed Ali and Siti Norbaiti Abdul Wahid - Mohammed Ali, Nur lzzatul Asma; Abdul Wahid, Siti Norbaiti (2018)
Reusable bags have given positive impact towards the customer's daily life especially when buying goods from the hypermarket. Reusable bags were introduced in the United States in 1977 and have adapted in Malaysia through "No Plastic Bag Day" campaign. The study examines the factors that influencing the intention to use reusable bags among hypermarket customer in Sungai Petani. A random sample of 380 customers were tested with questionnaire that including the items for the variables namely attitude, subjective norms and perceived behavioural control in relation with the intention to use reusable bags among hypermarket customer in Sungai Petani. The findings revealed that perceived behavioural control is the dominant factor that influencing the intention to use reusable bags whereby the variables have the most significant influence on the intention to use reusable bags. It is due to the customer that has the ability of enacting the actions as mentioned in the Theory of Planned Behaviour (TPB) whereby when there is good control towards the perceived behavioural, it will support the individual to perform more the action. Thus, this study have contribute in investigating more the relationship between attitude, subjective norms (significant others influence) and perceived behavioural control on the intention to use reusable bags among hypermarket customer.